1998
DOI: 10.1093/humrep/13.4.799
|View full text |Cite
|
Sign up to set email alerts
|

11Beta-hydroxysteroid dehydrogenase type 2 in human pregnancy and reduced expression in intrauterine growth restriction

Abstract: The type 2 isoform of 11beta-hydroxysteroid dehydrogenase (11beta-HSD2), which inactivates cortisol (F) to cortisone (E), has been suggested to play a role in the ontogeny of the fetal pituitary-adrenal axis and also protect the developing fetus from the deleterious effects of circulating maternal glucocorticoids. The abundance of 11beta-HSD2 in the placenta and other fetal tissues was inferred from the F/E ratio in 17 term deliveries in both umbilical arterial (1.73 +/- 0.24, mean +/- SE) and umbilical venous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
158
1
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(171 citation statements)
references
References 39 publications
10
158
1
2
Order By: Relevance
“…Studies have shown that 11 -HSD2 is expressed in the placental trophoblast (Brown et al 1993, Krozowski et al 1995, Sun et al 1997. The capacity for 11 -HSD2 to inactivate glucocorticoids in the placenta is very powerful, and this is supported by the placenta being the most abundant source of the enzyme, per mg of wet weight tissue (Shams et al 1998). 11 -HSD2 expression increases to term in the human, baboon and rat placenta (Burton & Waddell 1994, Shams et al 1998, Pepe et al 1999.…”
Section: -Hsd2 Localisationmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that 11 -HSD2 is expressed in the placental trophoblast (Brown et al 1993, Krozowski et al 1995, Sun et al 1997. The capacity for 11 -HSD2 to inactivate glucocorticoids in the placenta is very powerful, and this is supported by the placenta being the most abundant source of the enzyme, per mg of wet weight tissue (Shams et al 1998). 11 -HSD2 expression increases to term in the human, baboon and rat placenta (Burton & Waddell 1994, Shams et al 1998, Pepe et al 1999.…”
Section: -Hsd2 Localisationmentioning
confidence: 99%
“…The capacity for 11 -HSD2 to inactivate glucocorticoids in the placenta is very powerful, and this is supported by the placenta being the most abundant source of the enzyme, per mg of wet weight tissue (Shams et al 1998). 11 -HSD2 expression increases to term in the human, baboon and rat placenta (Burton & Waddell 1994, Shams et al 1998, Pepe et al 1999. In contrast, in the mouse placenta expression is reduced from gestation day 13 (term=19·5 days) (Brown et al 1996, Condon et al 1997.…”
Section: -Hsd2 Localisationmentioning
confidence: 99%
“…Previous human studies have demonstrated that there was a significant reduction in 11b-HSD2 enzyme activity in placentas from deliveries complicated by IUGR, and further studies demonstrated that there were also reductions in placental HSD11B2 gene expression. [17][18][19][20][21] How to explain the reduced placental HSD11B2 gene expression in IUGR newborns? Although mutations in HSD11B2 gene were detected in all patients with the syndrome of apparent mineralocorticoid excess, which was due to 11b-HSD2 deficiency, 22 no mutation was found in HSD11B2 gene from DNA extracted from IUGR placentas.…”
Section: Introductionmentioning
confidence: 99%
“…The enzyme 11β-hydroxysteroid dehydrogenase-2 (11β-HSD-2) has been isolated in the human placenta and likely accounts for the relatively low transfer of maternal cortisol to the fetus by converting cortisol to its inactive form cortisone (Benediktsson et al, 1997;Bernal, Flint, Anderson, & Turnbull, 1980). 11β-HSD-2 shows steady increases throughout gestation until the last few weeks of gestation when decreases in 11β-HSD-2 are observed (Lopez Bernal, Anderson, & Turnbull, 1982;Murphy & Clifton, 2003;Sandman et al, 2003;Schoof et al, 2001;Shams et al, 1998). Although, 11β-HSD-2 provides protection for the fetus from maternal cortisol, it does not provide complete protection; thus, some maternal cortisol continues to reach the fetus.…”
Section: Introductionmentioning
confidence: 99%